Exploring Reflective Practice for Professional Growth: Insights from Nepali English Teachers (SNPRC Journal, 2026)
Reflective practice fuels English teachers for a meaningful learning and brighten students’ learning experiences. Reflective practice enables researchers to develop into critical, creative, and analytical thinkers. The practice of reflection also aligns with the ideas of human activity, where individuals record their learning, reflect, measure, assess, and evaluate the learning process. This study aimed to explore how English teachers in Nepal engage in reflective practice. A narrative inquiry design also embraced within an interpretive paradigm. I used the Zoom app to conduct semi-structured interviews using purposive sampling. Five participants were chosen to produce genuine data. I coded and thematized the interview transcription to reach conclusions. The study explored respondents' experiences under an interpretive paradigm to reveal nuances in reflective practices. Findings show reflective practice for self-improvement, role of ICT (Information and Communication Technology) in transforming reflective instruction, and reflective practice as salient feedback. Reflective practice thrives in inclusiveness and invaluable learning while embracing ICT to identify learning gaps. Participants highlighted transformative learning through storytelling, feedback, journals, motivation, and context-specific teaching. The implications highlight enhancement of teachers’ leadership skills, ICT integration and leadership skills and a commitment to continuous learning.